The hybrid protein interactome contributes to rice heterosis as epistatic effects. (13th December 2019) - Li, Hong; Jiang, Shuqin; Li, Chen; Liu, Lei; Lin, Zechuan; He, Hang; Deng, Xing‐Wang; Zhang, Ziding; Wang, Xiangfeng
Summary: Heterosis is the phenomenon in which hybrid progeny exhibits superior traits in comparison with those of their parents. Genomic variations between the two parental genomes may generate epistasis interactions, which is one of the genetic hypotheses explaining heterosis. We postulate that protein−protein interactions specific to F1 hybrids (F1 ‐specific PPIs) may occur when two parental genomes combine, as the proteome of each parent may supply novel interacting partners. To test our assumption, an inter‐subspecies hybrid interactome was simulated by in silico PPI prediction between rice japonica (cultivar Nipponbare) and indica (cultivar 9311). Four‐thousand, six‐hundred and twelve F1 ‐specific PPIs accounting for 20.5% of total PPIs in the hybrid interactome were found. Genes participating in F1 ‐specific PPIs tend to encode metabolic enzymes and are generally localized in genomic regions harboring metabolic gene clusters. To test the genetic effect of F1 ‐specific PPIs in heterosis, genomic selection analysis was performed for trait prediction with additive, dominant and epistatic effects separately considered in the model. We found that the removal of single nucleotide polymorphisms associated with F1 ‐specific PPIs reduced prediction accuracy when epistatic effects were considered in the model, but no significant changes were observed when additive or dominant effects were considered. In summary, genomic divergence widely dispersed between japonica and indica rice may generate F1 ‐specific PPIs, part of which may accumulatively contribute to heterosis according to our computational analysis. These candidate F1 ‐specific PPIs, especially for those involved in metabolic biosynthesis pathways, are worthy of experimental validation when large‐scale protein interactome datasets are generated in hybrid rice in the future. Significance Statement: Based on a simulated protein interactome in hybrid rice, inter‐subspecies protein interactions specific to F1 hybrids were proven to play an epistatic role in yield heterosis.